2017
DOI: 10.1007/s10529-017-2412-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the purine operon and energy generation in Bacillus amyloliquefaciens for guanosine production

Abstract: The combined modification strategy used in this study is a novel approach to improve the production of guanosine in industrial bacterial strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The gene purF encodes amidophosphoribosyltransferase, which is a rate-limiting enzyme in the production of purine nucleosides. 19 The transcription level of purF in strain IR-1−1 increased by 1323% compared to that of DW2 (Figure S1). Additionally, the transcription levels of yf kN and guaC, which encode 5′-nucleotidase and GMP reductase, respectively, were increased by 386% and 375% (Figure S1), and the concentrations of intracellular hypoxanthine, guanine, and adenine were increased by 9.27-, 2.39-, and 5.32-fold, respectively (Figure 2B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The gene purF encodes amidophosphoribosyltransferase, which is a rate-limiting enzyme in the production of purine nucleosides. 19 The transcription level of purF in strain IR-1−1 increased by 1323% compared to that of DW2 (Figure S1). Additionally, the transcription levels of yf kN and guaC, which encode 5′-nucleotidase and GMP reductase, respectively, were increased by 386% and 375% (Figure S1), and the concentrations of intracellular hypoxanthine, guanine, and adenine were increased by 9.27-, 2.39-, and 5.32-fold, respectively (Figure 2B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Dissolved oxygen plays an important role in the cell growth, especially in the industry‐scale fermentation processes. In B. subtilis , the aerobic respiratory system contains four terminal oxidases: cytochrome caa 3 , which is a cytochrome c oxidase, cytochrome aa 3, and bd , and a putative YthAB oxidase, which are quinol oxidases (Figure ) . Under aerobic conditions, cytochrome bd encoded by cyd plays a minor role during rapid growth, and the deletion of cyd increases the efficiency of energy generation .…”
Section: Resultsmentioning
confidence: 99%
“…Under aerobic conditions, cytochrome bd encoded by cyd plays a minor role during rapid growth, and the deletion of cyd increases the efficiency of energy generation . A previous study showed that the deletion of cyd resulted in a high guanosine yield in B. amyloliquefaciens XH7 . So we knocked out the cyd gene to investigate its effect on MK‐7 synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus has been recognized as the superior producing strains for the production of purine nucleoside. For example, Liao et al acquired 19 g/L of guanosine in Bacillus amyloliquefaciens after optimizing purine operon and energy generation . The production of inosine in Bacillus subtilis was increased to 7.6 g/L when the synthesis of adenosine monophosphate and the degradation of inosine were blocked by deletion of the adenylosuccinate synthase gene ( purA ) and the purine nucleoside phosphorylase (PNP) gene ( deoD ) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Liao et al acquired 19 g/L of guanosine in Bacillus amyloliquefaciens after optimizing purine operon and energy generation. 21 The production of inosine in Bacillus subtilis was increased to 7.6 g/L when the synthesis of adenosine monophosphate and the degradation of inosine were blocked by deletion of the adenylosuccinate synthase gene (purA) and the purine nucleoside phosphorylase (PNP) gene (deoD). 22 Deletion of the guaA gene encoding the GMP synthase and overexpression of the purA gene in B. subtilis resulted in the production of adenosine at a titer of 14.39 g/L.…”
Section: ■ Introductionmentioning
confidence: 99%